A study of business knowledge requirements for software projects. (22nd March 2021) - Mishra, Debasisha
Abstract : Purpose: This paper aims to explore the expertise level required in various kinds of business knowledge such as regulatory, domain, strategic, operation process and, business process to execute globally distributed software projects for development, re-engineering and maintenance projects in the Indian outsourcing software industry. Design/methodology/approach: This study adopted a questionnaire survey method to collect the expert responses for a knowledge management framework which is suggested in the literature for software development work. The questionnaire survey findings were verified by expert interviews. Findings: The research shows that there is a lot of similarity between re-engineering and maintenance projects for different kinds of business knowledge expertise requirements for execution. The development projects require higher expertise in all the business knowledge for execution. Research limitations/implications: The research work studies the business knowledge required for the execution of development, re-engineering and maintenance projects in Indian outsourcing software projects. However, the project's characteristics can vary drastically for a single kind of project. So the study cannot be generalized and instead should be used as a tool for learning. Practical implications: The research findings can be used by software project managers to get insight into project planning, which can help the division of work between the onsite, offshore team and individual work allocation. Originality/value: The research is novel as there are very few previous attempts to find the business expertise needed to execute various kinds of software projects in the Indian outsourcing industry.